VARIATIONS IN MG/CA, NA/CA, AND SR/CA RATIOS OF CORAL SKELETONS WITH CHEMICAL TREATMENTS: IMPLICATIONS FOR CARBONATE GEOCHEMISTRY - Mitsuguchi T.; Uchida T.; Matsumoto E.; Isdale P.J.; Kawana T. (My University, 2001)
We made a systematic examination into the effects of chemical treatments on Mg/Ca, Na/Ca, and Sr/Ca ratios of coral skeletons. Five skeletal samples were cut from modern and fossil corals of the genus Porites. Each sample was ground into powder, and replicate subsamples were taken and split into four groups. One group was left untreated as the control group. The other three groups were treated cumulatively with distilled/deionized water (DDW), 30% H2O2, and weak HNO3, with one group separated after each treatment step. The H2O2 and HNO3 treatments incurred partial dissolution of the skeletal powder and thus resulted in considerable sample loss. All the groups were determined for the elemental ratios. The Mg/Ca and Na/Ca ratios showed decreases or little changes with the DDW treatment, and then increased with the H2O2 and HNO3 treatments. The Mg/Ca and Na/Ca variations were closely parallel throughout the treatment sequence. The Sr/Ca ratio showed slight or little variation throughout the treatment sequence. These results reflect fine-scale elemental distribution in the skeletons. The Mg/Ca and Na/Ca decreases with the DDW treatment can be ascribed to removal of adsorptive Mg and Na from the skeletal surface. The Mg/Ca and Na/Ca increases with the latter treatments reflect enrichments in Mg and Na at the innermost portion of the skeletons (i.e., around the center of calcification). The Mg/Na ratio of the adsorptive phase is approximately the same as that of the skeletons. The covariation of Mg and Na in the adsorptive and skeletal phases indicates that Mg and Na behave similarly both in adsorption onto the skeletal surface and in the skeletogenesis. Sulfate ion (SO42-) may participate in the Mg and Na behaviors. The Sr/Ca variation indicates that Sr is distributed almost homogeneously in the skeletons with little adsorptive fraction. Attention should be paid to the effects of chemical treatments associated with the fine-scale elemental heterogeneity, especially if coral Mg/Ca and Na/Ca ratios are used for paleoenvironmental analysis.